2008
DOI: 10.1007/s11669-008-9391-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations in the System TiO2-V2O x under Oxidizing and Reducing Conditions

Abstract: The target of this work was to investigate the phase development in the catalyst system consisting of TiO 2 (Anatase) and V 2 O 5 (Shcherbinaite) under several gas atmospheres. Thus a set of V 2 O 5 / TiO 2 specimens was prepared by ball milling and exposed to subsequent annealing in air and feed gas in the temperature range from 400 to 700°C. The XRD-results showed that the initial phases Anatase and Shcherbinaite remain stable for all atmospheres containing oxygen. In the temperature range above 525°C the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Little liquidus and solidus data have been reported for the Ti-V-O system in air (see Table 1). However, in two recent studies by Habel et al [4,5] a wide solubility range of V 2 O 5 in rutile crystal structure was reported. The focus of their work was on phase development during catalyst processing under oxidizing conditions.…”
Section: Liquidus and Solidus Datamentioning
confidence: 94%
See 2 more Smart Citations
“…Little liquidus and solidus data have been reported for the Ti-V-O system in air (see Table 1). However, in two recent studies by Habel et al [4,5] a wide solubility range of V 2 O 5 in rutile crystal structure was reported. The focus of their work was on phase development during catalyst processing under oxidizing conditions.…”
Section: Liquidus and Solidus Datamentioning
confidence: 94%
“…In this study, we investigate the Ti-V-O system in air, which in turn will contribute to thermochemical database for M-V-O systems (where M refers to metallic elements like Na, K, Ca, Mg, Ti, Cr, Mn, Fe, Al, and Si) under oxidizing conditions. Only a few studies have partially investigated phase equilibria of Ti-V-O in air and at lower oxygen partial pressures [2,3,4,5]. Nevertheless, the Ti-V-O system was thermodynamically evaluated by Enomoto [6] and later again by Yang et al [7] in response to new experimental phase diagram data obtained under relatively reducing conditions [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,21,22], doping with vanadium should provide realization of transparent and semiconducting films based on a TiO 2 matrix. Ti-V oxides can form either n or p type conduction depending on revealed phases [23,24]. In previous authors' work [18] in TiO 2 -V 2 O 5 phase composition, semiconducting properties with the p-type of electrical conductivity rarely found in transparent electronics has been achieved [18] ion concentration, acting as a donor impurity.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, in this paper studies of the structural, electrical and antistatic properties of Ti0 2 thin films have been presented. For modification of dielectric nature of Ti0 2 and obtain semiconductive, dissipative thin films doping with different amount of vanadium [6,7] has been applied.…”
Section: Introductionmentioning
confidence: 99%